Identities : time, difference, and boundaries - Friese, Heidrun, 1958-; Assmann, Aleida (Making sense of history., 2002)
"Identity" has become a core concept of the social and cultural sciences. Bringing together perspectives from sociology, anthropology, psychology, history, and literary criticism, this book offers a comprehensive and critical overview on how this concept is currently used and how it relates to memory and constructions of historical meaning.